PENGARUH IKLIM KOMUNIKASI DAN GAYA KOMUNIKASI TERHADAP KINERJA KARYAWAN DI SMA DWIJENDRA DENPASAR - Ni Nyoman Cipta Dewi; Redi Panuju (PROMOSI: Jurnal Program Studi Pendidikan Ekonomi, 2018)
This study aims to determine the influence of communication climate and communication style and also the performance of employees in SMA Dwijendra Denpasar.Communication plays an important role in all aspects, including to the school organization. In the school organization education is the important thing and as the major position in development because it is oriented towards improving the quality of human resources. The quality of human resources is influenced by employee performance (teacher) itself. The communication climate approach and communication style also influenced employee performance marked by an increase in the number of new student enrollments from year to year.  This type of research is explanatory or confirmatory research. While the population in this study was employees in SMA Dwijendra and samples using saturated sample technique with total sampling is 70 peoples. Collected data were using questionnaire with Likert scale model, while the analysis used multiple linear regression analysis with SPSS 22.0 for windows software. The results of this study obtained Fcount of 73.827 where Ftable 3.132, then Fcount> Ftabel. This shows that simultaneously communication climate and communication style significantly influence employee performance in SMA Dwijendra. Results coefficient of determination or R square is 0.688 its means that communication climate and communication style variables effect the performance is 68.8%, while the rest influenced by other variables not examined in this study. Based on these findings, it can be concluded that the communication climate and communication style together significantly influence the performance of employees at SMA Dwijendra Denpasar. Keywords: communication climate, communication style, employee performance.